2010
DOI: 10.1590/s0365-05962010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Imunomapeamento nas epidermólises bolhosas hereditárias

Abstract: Abstract:Immunological mapping, an immunofluorescence technique, is currently the method most used to diagnose and differentiate the principal types of hereditary epidermolysis bullosa, since this technique is capable of determining the level of cleavage of this mechanobullous disease Keywords: Collagen; Epidermolysis bullosa; Laminin; Fluorescence Microscopy Resumo: O imunomapeamento, uma técnica de imunofluorescência, é o método atual mais utilizado para o diagnóstico laboratorial e a diferenciação dos princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…10 Moreover, this Brazilian study also demonstrated widespread inter-familial and intra-familial variability in the clinical phenotypes of individuals with KS. 9 For the mutations identified in our patient, one mutation (p.Arg110X) has been reported previously in unrelated individuals from other countries although the other (p.Ala289GlyfsX7) appears to be novel and unique to this individual/family. The consequences of these mutations could be similar to those previously reported, i.e.…”
Section: Discussionsupporting
confidence: 54%
“…10 Moreover, this Brazilian study also demonstrated widespread inter-familial and intra-familial variability in the clinical phenotypes of individuals with KS. 9 For the mutations identified in our patient, one mutation (p.Arg110X) has been reported previously in unrelated individuals from other countries although the other (p.Ala289GlyfsX7) appears to be novel and unique to this individual/family. The consequences of these mutations could be similar to those previously reported, i.e.…”
Section: Discussionsupporting
confidence: 54%
“…As genetic differentiation is not available in most Brazilian cities, subtypes are usually distinguished by immunological and ultra-structural analysis. 32,33 Subclassification is important in determining prognosis (risk of mucosal involvement, development of malignancies and premature death), as well as in providing subsidies for genetic counseling. 32 …”
Section: Diagnosismentioning
confidence: 99%
“…These limitations can be overcome with the concomitant use of immunofluorescence to map the basement membrane in frozen tissue sections with a variety of antibodies, including laminin-1 and 5, collagen V, VII and XVII, bullous pemphigoid antigen, integrin α6β4 and plectin. 9,33 EM is a relatively expensive method and one that is not yet routinely performed. Immunohistochemical study uses a limited number of antibodies and can be a useful alternative.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…This level of cleavage can be easily demonstrated with monoclonal antibodies against collagen IV (the basement membrane), in so-called immunomapping. 1-3 DBE is secondary to inherited dysfunction of collagen VII, the protein that forms the anchoring fibrils, which adhere the basement membrane to the dermal collagen. 4,5 …”
Section: Introductionmentioning
confidence: 99%